CHINESE MEDICINE TERMINOLOGY (Journal of Oriental Studies, 2018)
In this article are written general concepts of the signs of distinction inherent in Chinese medicine. The formation of medical terminology associated with the differences of Chinese medicine is shown. In the process of studying Chinese medical terminology, it was found that their origin, that is, the beginning are connected with the natural philosophy of Yin-Yang, the theory of the Five Elements (Wu Xing). These statements make it clear that Chinese medical terminology is very unusual. Because Chinese medicine understands in its own way a person and his body. In this regard, the article examines the linguistic features of Chinese medical terminology.